Antimicrobial Stewardship in Rhode Island Long-Term Care Facilities: Current Standings and Future Opportunities. (17th May 2016) - Morrill, Haley J.; Mermel, Leonard A.; Baier, Rosa R.; Alexander-Scott, Nicole; Dosa, David; Kavoosifar, Sara; Reece, Rebecca; LaPlante, Kerry L.
Abstract : Our survey of antimicrobial stewardship practices among Rhode Island long-term care facilities demonstrated opportunities to develop formal programs. Results suggest infection preventionists are largely responsible for ensuring appropriate antibiotic use in long-term care facilities and there is a need for increased interdisciplinary access to individuals with antimicrobial stewardship expertise. Infect Control Hosp Epidemiol 2016;37:979–982